Morphometric analysis of seed and seedling development of maguey sacatoro (Agave angustifolia Haw.) - Hernández-Castro, Elías; López-Sandoval, Yoccira Yanet; Escobar-Álvarez, José Luis; Ramírez-Reynoso, Omar; Maldonado-Peralta, María de los Ángeles; Valenzuela-Lagarda, José Luis (Ecosistemas y Recursos Agropecuarios, 2022)
Agaves are native to America and have different uses, among which the obtaining of ﬁbers and the elaboration of alcoholic beverages stand out; This has caused a considerable decline in wild populations; Therefore, the objective was to morphologically characterize capsules and seeds, and evaluate the development of the maguey sacatoro (Agave angustifolia Haw.) seedling collected in different sites in the center and north of the state of Guerrero, Mexico, for their propagation by seed. For the morphometric analysis a single factor design (Locality) was used and for the seed quality variables, a bifactorial analysis (locality and immersion time). The results obtained were subjected to analysis of variance and tests of means (Tukey, p ≤ 0.05). Weight, height and width of the capsules and seeds were taken. The standard germination test and viability were performed with the tetrazolium test. Subsequently, the seedling development was evaluated; in three times of immersion in water (0, 24 and 48 h) and measurements were made in root, leaf and stem. Motuapa presented capsules with a higher number of seeds and normal seeds (241 and 140, respectively). The longest capsules were presented by Atetetla, Motuapa and Los Amates (5.37 ± 0.50, 5.10 ± 0.40 and 4.97 ± 0.36 cm, respectively), Ateteta had greater capsule width (2.63 ± 0.05 cm), germination (95%) and viability (89.4%). Therefore, the production of A. sacatoro seedling, through the use of seeds, can be a viable alternative.